2013
DOI: 10.1038/modpathol.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

No KRAS mutations found in gastrointestinal stromal tumors (GISTs): molecular genetic study of 514 cases

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. A great majority of GISTs is driven by pathological activation of KIT or platelet-derived growth factor receptor-α (PDGFRA), two closely related receptor tyrosine kinases. However, other genetic changes including gain-of-function BRAF mutations and loss of succinate dehydrogenase (SDH) complex activity have been identified in the subsets of KIT-, PDGFRA-wild type tumors. Genetic mutations affecting KIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
0
18
0
3
Order By: Relevance
“…The prevalence of KRAS mutation in GISTs ranges from <0.2% of all GISTs (Lasota et al, 2013) to, in our series of eight wild type GISTs, 11%. In 2012, Miranda et al first described the occurrence of KRAS mutations in GISTs in three patients, two of which harbored KIT mutations and one of which harbored a PDGFRA mutation.…”
Section: Discussionmentioning
confidence: 48%
“…The prevalence of KRAS mutation in GISTs ranges from <0.2% of all GISTs (Lasota et al, 2013) to, in our series of eight wild type GISTs, 11%. In 2012, Miranda et al first described the occurrence of KRAS mutations in GISTs in three patients, two of which harbored KIT mutations and one of which harbored a PDGFRA mutation.…”
Section: Discussionmentioning
confidence: 48%
“…9,18 Based on previous studies, the frequency of RAS mutations in imatinib-naive GISTs remains very low. 19 More recently, a KRAS G12V mutation at 29% allele frequency has been reported in an SDH-deficient highly malignant gastric GIST. 20 No PIK3CA, HRAS, and KRAS mutations were identified in 16 SDH-deficient GISTs analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Lasota et al reported about the absence of KRAS mutations in a large cohort of GISTs (n =514) [3] which, to the best of our knowledge, constitutes by itself about 60 % of cases so far studied for this molecular alteration [4][5][6][7]. Thus, considering the cumulative evidence produced so far, the actual possible prevalence of KRAS mutations in GISTs seems much lower than the one we hypothesized, possibly approaching 0.3 %.…”
mentioning
confidence: 57%